studi kasus Studi Kasus Penatalaksanaan Fisioterapi Pada Frozen Shoulder Dextra Ed Causa tendinitis rotator cuff dengan modalitas Short Wave diathermy (SWD) dan Terapi Latihan - Aprilia, Wachnipah; Susanti, Nur (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2025)
Frozen shoulder causes the capsule covering the shoulder joint to shorten and contract. Frozen Shoulder problems are pain, spasm, limited joint range of motion, muscle weakness and decreased functional activity. Physiotherapy examination includes examining pain with Visual Analogue Scale, spasm with palpation, range of motion with goniometer, muscle weakness with Manual Muscle Testing, and functional activity with Shoulder Pain And Disability Index. In this case the technology chosen is Short Wave Diathermy (SWD) and Exercise Therapy. The purpose of this study was to determine the effect of physiotherapy management on Rotator Cuff Rotator Tendinitis dextra e.c with SWD modalities and Exercise Therapy. This research was conducted at Kajen Hospital, Pekalongan Regency. The results of the study obtained 4 treatments as follows: (1) there was a decrease in motion pain (2) there was a decrease in spasm (3) there was an increase in ROM (4) there was an increase in muscle strength (5) there was an increase in functional activity. The conclusion of the study is that physiotherapy interventions with SWD modalities and Exercise Therapy can reduce problems that arise in Frozen Shoulder e.c Rotator Cuff Tendinitis conditions.